Condition of Mangrove Forest in the Village of Apar Pariaman Utara District Pariaman City West Sumatra Province - Alpian, Alpian; Efriyeldi, Efriyeldi; Thamrin, Thamrin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
Pariaman Utara District has the most extensive mangrove forest, which is 16.5 ha, in Apar Village the amount (6.0 ha). The purpose of this study was to determine the type and density of mangrove forests and to determine the condition of mangrove forests by determining the percentage of canopy cover in Apar Village. The method used in this research is a survey method, where the data collected is data obtained directly from the field which is then analyzed the data. The research procedure consisted of several stages, namely, collecting density data at 3 stations. Each station consisted of 3 straight line transects along 50 meters from the sea and estuary to land with a position perpendicular to the coast and having a distance between transect lines of 50 meters. In each transect line there are 3 plots arranged in a zigzag manner with a size of 10 m x 10 m for the tree category mangrove community structure. Retrieval of canopy cover photo data which was then analyzed by hemispherical photography. The results of measurements of water quality from the research location were temperature 29 - 30 ° C, salinity 4 - 5 ‰ and pH of the waters were 6-7. The composition of mangroves in the research locations were Sonneratia caseolaris, Sonneratia alba, Rhizophora mucronata, Nypa fructicans. Density at station I, 1700.00 trees/ha, station II 1311.11 trees/ha and station III 1888.89 trees/ha. Canopy cover at station I, 80.65%, station II, 58.46% and station III, 83.21%